Pengembangan Buku Saku Submateri Bioteknologi Konvensional dari Hasil Isolasi dan Filogenetik BAL pada Mandai Fermentasi Kulit Cempedak (Artocarpus champeden): (Development of a Pocket Book on Conventional Biotechnology Sub-Materials from the Isolation and Phylogenetic Results of BAL in the Fermentation of Cempedak Skin (Artocarpus champeden)) - Kumalasari, Muthia; Fitri Yeni, Laili; Yokhebed, Yokhebed (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
This study aims to develop a pocket book on conventional biotechnology sub-material developed from the isolation, characterization, and phylogenetic relationships of lactic acid bacteria in mandai. The research employs a Research and Development (R&D) approach using the ADDIE model. The ADDIE model consists of Analysis, Design, Development, Implementation, and Evaluation. This study utilizes three stages of the ADDIE model: Analysis, Design, and Development. During the analysis stage, needs were identified through interviews with biology teachers in grade X at SMA Negeri 1 Sampit, which revealed the absence of learning media based on local potential. The design stage produced a pocket book design based on the learning outcomes of the Merdeka Curriculum, incorporating conventional biotechnology content, research results on the isolation and characterization of bacteria, and the phylogenetic relationships of lactic acid bacteria. The development stage produced a 9 x 12 cm pocket book consisting of 34 pages, which was then validated by five validators. The validation results showed an average Content Validity Ratio (CVR) of 0.99, which is considered valid. Thus, the pocket book is deemed suitable for use as a learning medium for the sub-subject of Conventional Biotechnology based on local potential at the high school level. Key words: Pocket book, Conventional Biotechnology, Mandai